2017
DOI: 10.1093/toxsci/kfx079
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Comparative Proteomics Reveals Silver Nanoparticles Alter Fatty Acid Metabolism and Amyloid Beta Clearance for Neuronal Apoptosis in a Triple Cell Coculture Model of the Blood–Brain Barrier

Abstract: Silver nanoparticles (AgNPs) enter the central nervous system through the blood-brain barrier (BBB). AgNP exposure can increase amyloid beta (Aβ) deposition in neuronal cells to potentially induce Alzheimer's disease (AD) progression. However, the mechanism through which AgNPs alter BBB permeability in endothelial cells and subsequently lead to AD progression remains unclear. This study investigated whether AgNPs disrupt the tight junction proteins of brain endothelial cells, and alter the proteomic metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Moreover, perturbation in oxidative phosphorylation and fatty acid metabolism were also observed in mouse neuroblastoma N2a exposed to silver ENMs [7]. A similar observation was made in human monocyte THP-1 cells treated with gold ENM, in which proteins involved in energy metabolism such as glucose-6-phosphate dehydrogenase and long-chain fatty acid-CoA ligase 1 were up-regulated [73].…”
Section: Cellular Responses To Enm Exposurementioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, perturbation in oxidative phosphorylation and fatty acid metabolism were also observed in mouse neuroblastoma N2a exposed to silver ENMs [7]. A similar observation was made in human monocyte THP-1 cells treated with gold ENM, in which proteins involved in energy metabolism such as glucose-6-phosphate dehydrogenase and long-chain fatty acid-CoA ligase 1 were up-regulated [73].…”
Section: Cellular Responses To Enm Exposurementioning
confidence: 71%
“…Applications of ENMs in diagnostic assays and drug delivery systems for treatment of human diseases have also increased substantially in the last decade [35]. However, the potential risk to human health due to the prevalent use and potential exposure to many kinds of ENMs through ingestion, inhalation, or even penetration via the skin is also an important concern [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…We have studied effects in intestinal Caco‐2 cells (Oberemm et al, ), while Georgantzopoulou and colleagues have studied the effects of nanoparticulate and ionic silver on a Caco‐2/HT29‐MTX co‐culture (Georgantzopoulou et al, ). Additional analyses have been carried out with the human intestinal cell line LoVo (Miethling‐Graff et al, ; Verano‐Braga et al, ) and some other non‐liver cell lines (Driessen et al, ; Huang et al, ; Lin et al, ). In essence, these proteomic analyses confirmed the important role of reactive oxygen species and oxidative stress in silver toxicity, and provided evidence for inflammatory responses, modulation of cell cycle and cell death, as well as alterations in post‐translational protein modification and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid metabolism is a toxicologically relevant cellular function, which was predicted to be altered by silver in our study, but this molecular pathway did not explicitly pop up in previous transcriptome analyses (Kawata et al, ; Sahu et al, ). However, studies in other cell lines have clearly shown an influence of nanosilver on mitochondrial function and fatty acid metabolism at the mRNA, protein and metabolite levels (Chen et al, ; Lin et al, ; Oberemm et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation